Chulanova G., Kuzmenko I. Lexical bearer of the expressivity - Chulanova G.; Kuzmenko I. (Philological Treatises, 2020)
The article in question deals with the lexical bearer of the expressivity in the advertising. Herewith much attention is given to the usage of different figures of speech in advertising texts.